1995
DOI: 10.1039/ft9959101631
|View full text |Cite
|
Sign up to set email alerts
|

Temperature dependence of the rate of reaction of OH with some aromatic compounds in aqueous solution. Evidence for the formation of a π-complex intermediate?

Abstract: The rates of reaction of OH with benzene, chlorobenzene, nitrobenzene, benzoate ion and benzoic acid have been measured in aqueous solution up to 200 "C using pulse radiolysis to generate OH. The temperature dependence of the observed rate constant, kobs , is essentially the same for each compound and kobs changes by less than three-fold between 20°C and 200°C. The kinetic data are consistent with a mechanism whereby OH reversibly forms a n-complex with the aromatic compound, irrespective of the substituent on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
103
0

Year Published

1995
1995
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(117 citation statements)
references
References 21 publications
14
103
0
Order By: Relevance
“…Curve (0) in Fig. 9 represents the spectrum recorded during pulse radiolysis of N 2 O-purged 1 mM benzene at alkaline pH indicating HO-adduct of benzene, i.e., hydroxy cyclohexadienyl type radical, which is having absorption in UV region (k max around 310 nm) and is similar to the reported one [42][43][44]. In contrast to hydroxy cyclohexadienyl radical in the benzene pulse radiolysis spectrum, a spectrum having two bands with maxima around 400 and 380 nm was observed during electron pulse irradiation of filtrate solutions obtained from photolysis experiments.…”
Section: Resultssupporting
confidence: 51%
“…Curve (0) in Fig. 9 represents the spectrum recorded during pulse radiolysis of N 2 O-purged 1 mM benzene at alkaline pH indicating HO-adduct of benzene, i.e., hydroxy cyclohexadienyl type radical, which is having absorption in UV region (k max around 310 nm) and is similar to the reported one [42][43][44]. In contrast to hydroxy cyclohexadienyl radical in the benzene pulse radiolysis spectrum, a spectrum having two bands with maxima around 400 and 380 nm was observed during electron pulse irradiation of filtrate solutions obtained from photolysis experiments.…”
Section: Resultssupporting
confidence: 51%
“…Similar temperature dependences for reaction of hydroxyl radicals with aromatic compounds have recently been reported and discussed (20).…”
Section: Radiolysis Studies Of 1-hexyn-3-01supporting
confidence: 49%
“…p-Complexes of radicals to aromatic compounds are known, and even for a radical as reactive as COH it has been shown that such a complex has to be postulated as an intermediate in its reaction with benzene to the hydroxycyclohexadienyl radical. [93] However, a p-complex of a strongly oxidizing radical such as COH with a strongly reducing radical such as CQH/QC À (as postulated in ref. [60]) will immediately collapse either by electron transfer of by recombination.…”
mentioning
confidence: 98%